Osteochondroma of the condyle - Karthikeya Patil; V G Mahima; Sujith Shetty; S Sudhakar (Wolters Kluwer Medknow Publications, 2009)
Osteochondroma, also known as osteocartilaginous exostosis, is a benign cartilage capped outgrowth attached to the underlying skeleton by a short stalk. Osteochondroma is frequently seen in the axial skeleton but rarely occurs in the craniofacial skeleton. We report a case of osteochondroma arising from the right mandibular condyle.